Prophylactic Mesh Placement During Formation of an End-colostomy Reduces the Rate of Parastomal Hernia: Short-term Results of the Dutch PREVENT-trial. Issue 4 (April 2017) - Brandsma, Henk-Thijs; Hansson, Birgitta M. E.; Aufenacker, Theo J.; van Geldere, Dick; Lammeren, Felix M. V.; Mahabier, Chander; Makai, Peter; Steenvoorde, Pascal; de Vries Reilingh, Tammo S.; Wiezer, Marinus J.; de Wilt, Johannes H. W.; Bleichrodt, Robert P.; et al.
Abstract : Objective: The aim of this study was to investigate the incidence of parastomal hernias (PSHs) after end-colostomy formation using a polypropylene mesh in a randomized controlled trial versus conventional colostomy formation. Background: A PSH is the most frequent complication after stoma formation. Symptoms may range from mild abdominal pain to life-threatening obstruction and strangulation. The treatment of a PSH is notoriously difficult and recurrences up to 20% have been reported despite the use of mesh. This has moved surgical focus toward prevention. Methods: Augmentation of the abdominal wall with a retro-muscular lightweight polypropylene mesh was compared with the traditional formation of a colostomy. In total, 150 patients (1:1 ratio) were included. The incidence of a PSH, morbidity, mortality, quality of life, and cost-effectiveness was measured after 1 year of follow-up. Results: There was no difference between groups regarding demographics and predisposing factors for PSH. Three out of 67 patients (4.5%) in the mesh group and 16 out of 66 patients (24.2%) in the nonmesh group developed a PSH ( P = 0.0011). No statistically significant difference was found in infections, concomitant hernias, SF-36 questionnaire, Von Korff pain score, and cost-effectiveness between both study groups. Conclusion: Prophylactic augmentation of the abdominal wall with a retromuscular lightweight polypropylene mesh at the ostomy site significantly reduces the incidence of PSH without a significant difference in morbidity, mortality, quality of life, or cost-effectiveness.